Effects of Antihypertensive Drugs on Thyroid Function in Type 2 Diabetes Patients With Euthyroidism - Yang, Lijuan; Sun, Xiuqin; Zhao, Yi; Tao, Hong (Frontiers in Pharmacology, 2022)
Objective: There is little literature about whether antihypertensive drugs would affect thyroid function in patients with euthyroid type 2 diabetes, which was significant in maintaining a proper balance of thyroid function. A retrospective cohort study was conducted to evaluate the influence of antihypertensive drugs on thyroid function in patients with type 2 diabetes with euthyroidism. Design and Methods: The study involved dividing 698 patients with antihypertensive monotherapy into five groups according to the antihypertensive drugs they were treated with. Antihypertensive drugs included in this study were β-blockers, ACEI, ARB, and CCB. ANOVA and paired student t-tests were used to compare the thyroid function level between and within groups. Multiple logistic regression analysis was conducted to evaluate the association of antihypertensive drugs with thyroid function level. Results: Selective β1- adrenergic receptor blockers treatment was related to TSH, increasing in patients with diabetes and euthyroidism as shown by multiple logistic regression analysis. Gender, age, BMI, smoking habits, alcohol consumption, and other antihypertensive drug treatments were nonsignificant variables in this model. No significant influence on thyroid function was found among other antihypertensive drugs. Conclusion: These data show the TSH-lifting effect of selective β1-adrenergic receptor blockers in patients with type 2 diabetes with euthyroidism.